VOLATILIZAÇÃO DE AMÔNIA EM PASTAGEM ADUBADA COM FONTES NITROGENADAS - CHAGAS, Paulo Henrique Menezes das; BARBOSA, Willams Ferreira Sousa; LOPES, Karina Garcia; ALMEIDA, Rafael Lopes; COSTA, Geany Giovana Silva; ALVES, Ana Carolina (ANAIS DO ENIC, 2017)
-